Chapter View management in city-port landscapes. Livorno applicative experience - Scamporrino, Matteo (Proceedings e report, 2020)
The paper is a synthesis of a multi-year research path carried out by University of Florence with Livorno Port Authority. This research, although born and developed within a specific context, the port one, is part of a more general debate concerning the planning, design and evaluation of urban transformations at a visual and scenic level in complex and stratified territories with historical permanence. The ultimate aim of this contribution is represented by the results of the experiments on the tools for measuring the visual and scenic impact, known at disciplinary level as View Management.